Implementation of Maqashid Syariah in Sharia Business Transactions - Dhiyaa Meuthia Faiqah Erba; Nofrianto Nofrianto (AL-FALAH : Journal of Islamic Economics, 2022)
Purpose: This study aims to determine how the implementation of maqashid sharia in sharia business transactions such as Sharia Banking, Sharia Cooperatives and Sharia Insurance.Design/Method/Approach: This research is a descriptive research. This research was conducted by analyzing the implementation of maqashid sharia in sharia business transactions. This research uses a qualitative approach. The sources of this research are secondary data, and the data sources are obtained through various sources such as books, journals, or websites. The technique used in this research is to examine important notes or materials related to the object of researchFindings: Maqashid Syariah in sharia business transactions such as sharia banking, sharia cooperatives and sharia insurance has been implemented properly. It was proven byIslamic banks that help people achieve goodness and provide benefits for their lives and stay away from harm. In a Sharia Cooperative, the implementation of Maqashid Sharia is manifested in a sharia cooperative that can help prosper the lives of its members. Meanwhile, in Maqashid Syariah Insurance, it can be seen from Helping in the face of a risk.Organally/Value: The results of this study can be used as learning materials and knowledge for readers and financial institutions and can be used as a reference for learning about the implementation of maqashid sharia in Islamic financial institutions. Because, this study finds out how the implementation of maqashid sharia in Islamic financial institutions such as sharia insurance, sharia banking, and sharia cooperatives.